2014
DOI: 10.1002/mnfr.201300853
|View full text |Cite
|
Sign up to set email alerts
|

Moderate chronic administration of Vineatrol-enriched red wines improves metabolic, oxidative, and inflammatory markers in hamsters fed a high-fat diet

Abstract: Our studies suggest that RWV is capable of reversing the atherogenic process induced by an HF diet in hamster tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Therefore, in these groups, the decreases in hepatic and cardiac O 2 À production are not related to an increase in enzymatic antioxidant defenses, but rather to a sparing effect due to their direct antioxidant properties [30]. This has been reported in other studies [24,31] where dietary antioxidants (phenolics) consumption decreased endogenous antioxidant enzymes, scavenging oxygen radicals and reducing the requirement for cellular antioxidant defense. PON activity is another marker of oxidative stress.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Therefore, in these groups, the decreases in hepatic and cardiac O 2 À production are not related to an increase in enzymatic antioxidant defenses, but rather to a sparing effect due to their direct antioxidant properties [30]. This has been reported in other studies [24,31] where dietary antioxidants (phenolics) consumption decreased endogenous antioxidant enzymes, scavenging oxygen radicals and reducing the requirement for cellular antioxidant defense. PON activity is another marker of oxidative stress.…”
Section: Discussionsupporting
confidence: 53%
“…Triacylglycerols and glucose levels were measured in plasma (10 mL) using a Randox enzymatic kit and reagents from the Thermo Electron Corporation (Cergy Pontoise, France), respectively. Paraoxonase activity (PON) was determined using paraoxon as a substrate and measured by the increase in absorbance at 412 nm, as previously described [24]. Insulinemia (10 mL plasma) was determined using enzyme-linked immunosorbent assay (ELISA) kits (Mercodia AB, Uppsala, Sweden).…”
Section: Plasma Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in NFκB seen in both the wine and vodka group compared to the control echoes previous data in a similar hamster model, in which NFκB was upregulated in animals treated with wine versus a high-fat control. 22 That study also demonstrated a decrease in inflammatory signaling. The increase in levels of NFκB with the addition of wine and vodka in the ischemic tissue when compared to controls which was not seen in the non-ischemic myocardium further supports the importance of this inflammatory pathway in areas of ischemia.…”
Section: Discussionmentioning
confidence: 70%
“…LDL is bad cholesterol which causes the formation of plaque on the walls of arteries which can clog the arteries and reduce their elasticity. In contrast, HDL is good cholesterol which assists in the removal of LDL (Romain et al 2014). Consequently, honey is helpful in preventing the formation of plaque in the blood vessels, thus preventing complications such as atherosclerosis in diabetic patients.…”
Section: Role Of Honey In Diabetesmentioning
confidence: 99%